Construction of a haptic-based virtual reality evaluation of discrimination of stiffness and texture. Issue 1 (31st December 2022) - Dahan, Hodaya; Stern, Hodaya; Bitan, Noa; Bouzovkin, Anna; Levanovsky, Maya; Portnoy, Sigal
Abstract: Sensory impairments have a negative impact on performance. We designed and validated a haptic-based Virtual Reality (VR) system for the evaluation of discrimination of stiffness/texture and tested its agreement with current conventional tactile sensibility evaluations. Forty-four individuals (age 25.2 ± 4.1) performed three tactile tests: the newly constructed haptic-based VR system, the Shape/Texture Identification Test (STI), and the Moberg Pick-Up Test. Bland-Altman plots tested for agreement between the haptic-based VR system and the standard tests. We found very good agreements (>95% of the data points lies within ±2SD of the mean difference) between the haptic-based VR scores and the scores of the conventional tests, except in the cases of the STI trial, when performed with the non-dominant hand, and the Moberg Pick-Up Test when performed with the dominant hand with open eyes. The advantages of the haptic-based VR evaluation of discrimination of stiffness and texture and its agreement with standard tests of sensory loss might suggest that the system can be used in the clinical settings.